Fahr’s syndrome as the initial imaging characteristics of MELAS syndrome with a possible seizure activity and cardiac arrest: a case report - Zheng, Yan; Wu, Haohao; Zhang, Meng; Huang, Baogang; Yang, Junsu; Liu, Chuan; Wang, Hanmin; Du, Kang (Frontiers in Genetics, 2024)
This study reported a case of MELAS syndrome presenting as the initial imaging characteristics of Fahr's syndrome with "near" sudden unexpected death in epilepsy (SUDEP) and lateralized periodic discharges (LPD). The patient, a young boy, experienced loss of consciousness two days prior, which was followed by two limb and facial convulsions. He was later found in cardiac arrest during hospitalization, but regained consciousness gradually after receiving cardiopulmonary resuscitation and tracheal intubation. The patient exhibited short stature, intellectual disability, poor sports abilities, and academic performance since childhood, but had no family history. Emergency head computed tomography (CT) revealed high density calcification in bilateral caudate nucleus, lentiform nucleus, thalamus, and dentate nucleus with evidence of an acute process. The patient was transferred to the neurology department where he continued to recover consciousness, though he experienced dysarthria, left limb hemiplegia, and hemiparesthesia. Changes in head magnetic resonance imaging (MRI) findings were noted at admission, one month later, and six months later. LPD were observed in his video electroencephalogram. The CT urography indicated a narrow left ureteropelvic junction with left hydronephrosis, which was suggestive of ureteropelvic junction obstruction. Ultimately, a diagnosis of near-SUDEP was suspected in this patient, indicating a rare case of MELAS syndrome with near-SUDEP and LPD. The gene tests results revealed the presence of the mitochondrial DNA A3243G mutation, leading to the final diagnosis of MELAS syndrome. This case expands the clinical disease spectrum of the MELAS syndrome.